Dinamika Kebijakan Walikota Pekanbaru Nomor 148 Tahun 2020 Tentang Jasa Layanan Parkir: Studi Parkir Berbayar Mini Market di Kota Pekanbaru Tahun 2021 - Yoselia, Cindy (Brawijaya University, 2023)
The implementation of paid parking at Indomaret and Alfamart in Pekanbaru City has received many complaints from the public, this is because parking at the two minimarkets which was previously free has now become paid. However, the parking technical implementation unit stated that this policy aims to increase the original regional income of Pekanbaru City and wants to revive the community's small businesses. The research results show that there is a dynamic implementation of policies based on Pekanbaru Mayor Regulation Number 148 of 2020 due to the government's desire to increase local original income in order to increase city development and regulate parking according to applicable regulations. However, the community and the Pekanbaru City DPRD did not agree, so the Pekanbaru City Government reviewed the implementation of this policy so that a review was carried out with the Transportation Service and the Pekanbaru City DPRD.